Purification and properties of a coagulant proteinase isolated from bushmaster (Lachesis muta) venom (Serpentes: Viperidae) - Aragón-Ortiz, F. (Revista de Biología Tropical, 1986)
The venom of Lachesis muta is a rich source of a thrombin-like enzyme. Its coagulant proteinase was purified by DEAE -Sephadex A -50 followed by agmatine CH -Sepharose and gel filtration on Sephadex G-100. On polyacrylamide gel electrophoresis at pH 8.4 a single band was observed. Its molecular weight by gel filtration was 49,000. The coagulant and esterolytic activities toward human fibrinogen and Tame of the inudasa were 662 NIH units/mg of protein and 4.37 Δ OD225/min x 10-3 / µg / ml, respectively. These values represent 23 and 5.7 fold increase over the crude venom. The enzyme mudasa, was evaluated with serum from human patients at Hospital Nacional de Niños Dr. Carlos Sáenz Herrera and found to be 21 valuable reagent for the quantification of fibrinogen on heparinized plasma.